The Big Chill: Opportunities for, and Challenges to, Advanced Biopreservation of Organs for Transplantation - Capron, Alexander M.; Pruett, Timothy L.; Childress, James F. (The Journal of law, medicine & ethics, 2024)
The application of advanced biopreservation to organs donated for transplantation may make possible their indefinite storage and thereby improve the utility and equity they provide to patients. The technology is still at a preclinical stage, with many difficult, scientific issues that remain to be answered. At the moment, however, the actual capabilities of the technology are too indefinite to begin formulating the statutes, regulations, and ethical guidance that will be needed to obtain the benefits expected from its use.